Hydrogel Development for Rotator Cuff Repair - Xu, Zhengyu; Fang, Yifei; Chen, Yao; Zhao, Yushuang; Wei, Wei; Teng, Chong (Frontiers in Bioengineering and Biotechnology, 2022)
Rotator cuff tears (RCTs) are common in shoulder disease and disability. Despite significant advances in surgical repair techniques, 20-70% of patients still have postoperative rotator cuff dysfunction. These functional defects may be related to retear or rotator cuff quality deterioration due to tendon retraction and scar tissue at the repair site. As an effective delivery system, hydrogel scaffolds may improve the healing of RCTs and be a useful treatment for irreparable rotator cuff injuries. Although many studies have tested this hypothesis, most are limited to laboratory animal experiments. This review summarizes differences in hydrogel scaffold construction, active ingredients, and application methods in recent research. Efforts to determine the indications of hydrogel scaffolds (with different constructions and cargos) for various types of RCTs, as well as the effectiveness and reliability of application methods and devices, are also discussed.